REPRESENTATIONS OF CHILDREN OF YOUNGER PRESCHOOL AGE ABOUT THE CULTURE OF HUMAN HEALTH - Pradun, Inna; Shlat, Natalia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article deals with the problem of representations of modern children 3-4 years of age about the culture of human health. The authors analyze different approaches to the structure of the phenomenon "culture of health"; specify the place of culture health in the culture of the personality of the preschool child, the teacher's role in the formation of childrenʼs health culture. The article describes an empirical study of actual representations of children of younger preschool age about the culture of health: the diagnostic tools are characterized, the procedure of diagnosis is described, and the results are analyzed. The authors identify the specific representations of children 3-4 years of age about the culture of health, make a conclusion about representations which are typical for modern children of younger preschool age. The results of the study can be used as a basis for designing the content of the pedagogical work on the formation of components of the preschoolersʼ health culture.